Learning and teaching with Geomedia - Jekel, Thomas; Sanchez, Eric; Gryl, Inga; Juneau-Sion, Caroline; Lyon, John (Geographer) (Cambridge Scholars Publishing, 2014)
"Learning and Teaching with Geomedia provides a theoretical and practical introduction to a field explicitly aimed at secondary education. The first section consists of three scientific papers introducing the dimensions of the emerging geoinformation society. The second section of the book is specifically dedicated to teacher trainers and teachers. The introductory section provides an overview of the development of geomedia and envisions a roadmap of technological development ahead; a discussion of everyday geomedia applications and geomedia use; and, finally, pedagogical approaches using geomedia in secondary education."--